Drastic swelling of lipid oligobilayers by polyelectrolytes: a potential molecular model for the internal structure of lubricating films in mammalian joints - Schwörer, Felicitas; Trapp, Marcus; Xu, Xiao; Soltwedel, Olaf; Dzubiella, Joachim; Steitz, Roland; Dahint, Reiner (Langmuir, 2017)
Osteoarthritis is the most common arthropathy in western civilization. It is primarily caused by the degeneration of lipid-coated cartilage, leading to increased friction in joints. Hyaluronic acid (HA), a negatively charged polysaccharide and the main component of the synovial fluid, is held responsible for joint lubrication. It is believed that HA, adsorbed to the lipid-coated cartilage, forms a protective layer against wear. Studies have shown that the concentration and molecular weight (MW) of HA are reduced in joints suffering from osteoarthritis. On the basis of these observations, local joint injections of HA or mixtures of HA and surface-active phospholipids (SAPLs) have been applied as medical cures to restore the functionality of the joints in a procedure called viscosupplementation. However, this cure is still disputed, and no consensus has been reached with respect to optimum HA concentration and MW. To provide detailed insight in the structural rearrangement of lipid films upon contact with HA or polymeric analogues, we studied the interaction of the polyelectrolyte poly(allylamine hydrochloride) (PAH) with surface-bound oligobilayers of 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) by neutron reflectivity (NR) and ellipsometry. Using this model system, we found a drastic swelling of the lipid films as a function of PAH concentration, whose strength compares to that in previous studies on HA incubation. In contrast, no significant dependence of film thickness on PAH MW was observed. A detailed picture of the film architecture was developed which inter alia shows that charged PAH is adsorbed to the lipid headgroups, leading to electrostatic repulsion. The swelling behavior is well explained by the equilibrium of Coulomb and van der Waals interactions in a DLVO-based model. Our detailed structural analysis of the PAH/lipid interfacial layer may help to elucidate the mechanisms of viscosupplementation and derive a structure-function relationship for the lubricating interface in mammalian joints.
Gesehen am 04.09.2019